A Double-Blind, Randomized, Controlled Trial of Topical Polysporin Triple Compound Versus Topical Mupirocin for the Eradication of Colonization with Methicillin-Resistant Staphylococcus aureus in a Complex Continuing Care Population. Issue 3 (2009) - O'Grady, S; Hirji, Z; Pejcic-Karapetrovic, B; Fung, S; Dedier, H; Takata-Shewchuk, J; Zhang, K; Conly, J
Abstract : BACKGROUND: Intranasal mupirocin or Polysporin Triple (PT) ointment (polymyxin B, bacitracin, gramicidin), in combination with chlorhexidine body washes, have been used for eradicating methicillin-resistant Staphylococcus aureus (MRSA), but no comparative studies have been done. METHODS: A double-blind, randomized, controlled clinical trial to compare the efficacy of mupirocin versus PT ointment in combination with chlorhexidine body washes in eradicating MRSA carriage was conducted. Asymptomatic MRSA carriers, medically stable and at least 18 years of age who were patients on medical wards, received twice daily application of either mupirocin or PT ointment to the anterior nares plus once daily 2% chlorhexidine body washes for seven days. Follow-up swabs from multiple sites using broth enrichment were conducted at 48 h, and one, two, four, eight and 12 weeks. RESULTS: Of 103 patients eligible for analysis (54 mupirocin; 49 PT), no significant differences between the two groups with respect to baseline demographics, risk factors for MRSA or MRSA colonization sites were noted. At 48 h, 35 of 54 (65%) patients in the mupirocin group versus 15 of 49 (31%) in the PT group (P=0.001) were found to be MRSA negative at all sites. Significant differences were observed at one and two weeks but were not maintained at other intervals. In those with complete microbiological follow-up, MRSA eradication at all sites occurred in 12 of 39 (30.8%) mupirocin- and one of 36 (2.8%) PT-treated patients (P=0.001). CONCLUSION: Both agents demonstrated poor efficacy and PT was significantly less efficacious than mupirocin at 12 weeks in eradicating MRSA from all sites.